Expert consultation: factors influencing end-of-life decision-making for dairy cattle across the United States supply chain - Edwards-Callaway, Lily, author; McBride, Brianna, author; Machuca, Erica, author; Dean, Lauren, author; Sayre, Kira, author; Cramer, Catie, author; Román-Muñiz, Noa, author; Keller, Kayleigh, author; Stallones, Lorann, author; Manriquez, Diego, author; MDPI, publisher (Colorado State University. Libraries, 2024)
The end-of-life (i.e., on-farm euthanasia and culling, including fitness for transport to slaughter) of a dairy cow or calf is preceded by a series of decisions often influenced by many complex factors. The aim of this study was to utilize the opinions of experts with roles in the dairy supply chain to identify factors that influence end-of-life decision-making for dairy cattle. Twenty experts serving in supporting roles in the dairy supply chain participated in a survey containing 17 open-ended questions. Of the participants, 55% (n = 11) identified as veterinarians and the remaining 45% (n = 9) participated in other segments of the dairy supply chain. Twelve themes were identified in the qualitative analysis of survey responses. The themes included: Training and Resources, Cattle Health Management, Decision-Making Criteria, Company Culture, Personal Beliefs, Human Well-Being, Animal Welfare, Economics, Guidelines and Inspections, Consumer Perceptions, Supply Chain Considerations, and Communication. Experts indicated that training programs should address euthanasia or fitness-for-transport criteria, the knowledge of common health conditions, and information about what happens to cattle after leaving the dairy. Additional influencing factors included personal beliefs, economics, company culture, and supply chain considerations.
Keywords: animal welfare; dairy supply chain; end-of-life; euthanasia; fitness to transport